Pengendalian Stok Spareparts Mobil Dengan Metode EOQ dan Min-Max Inventory - Mia Juliana Siregar (Jurnal Serambi Engineering, 2021)
This research was conducted in the distributor of car spare parts and the object studied was car glass glue. This item is a product that experiences a stacking stock in the warehouse, so it needs inventory control to reduce the stacking stock. The character of the product which does not have expired date as long as it is not used and small size, the company never make an optimal estimate of the order, so the activity of ordering goods is only based on its own estimates. The method used in this research is EOQ to obtain the economical amount of the product to be ordered. The calculation process using EOQ method is done against 2019 sales data predicted to 2021 using Trend Linear forecasting method, with function form is Y=1,8776x+256,21. Furthermore, the minimum and maximum stock quantity is determined using the Min-Max Inventory method. From the result of the study found that the economic Q per ordered is 386 pcs with the frequency of bookings 8 times a year. The minimum inventory is 108 pcs and the maximum is 144 pcs with the amount of safety stock is 72 pcs and ROP is 108 pcs. By using EOQ method, the company can make savings of Rp3,939,330 per year and reduce storage cost by Rp10,119,635 per year.